Community Managed Protected Areas Conserve Aboveground Carbon Stocks: Implications for REDD+ - Alejo, Camilo; Walker, Wayne S.; Gorelik, Seth R.; Potvin, Catherine (Frontiers in Forests and Global Change, 2022)
Protected Areas (PAs) represent a broad spectrum of outcomes and governance systems. Among PAs, Community Managed PAs have emerged from communities that are not exclusively indigenous and have developed social organizations to acquire land rights, participate in forest governance, and in some cases, engage in REDD+. However, regardless of the scale or counterfactual, there is no clear consensus about Community Managed PAs’ effectiveness in forest conservation and climate change mitigation. Furthermore, previous studies have been devoted to estimating PAs’ effects on deforestation before REDD+ projects began to operate. Based on Community Concessions in Petén (Guatemala) and Extractive Reserves in Acre (Brazil), we analyzed Community Managed PAs’ temporal and spatial effects on carbon stocks and avoided emissions relative to unprotected lands, other Sustainable Use PAs (IUCN V-VI), and Strict PAs (I-IV). We used carbon density maps, matching methods, geographic discontinuity designs, and sensitivity analysis between 2003 and 2015. After controlling for the influence of market access and agriculture suitability, our analysis shows that Community Managed PAs were more effective than Other Lands (i.e., unprotected) and Sustainable Use PAs, and at least as effective as Strict PAs, in preserving carbon stocks and avoiding emissions. For instance, relative to Other Lands between 2011 and 2015, Community Managed PAs resulted in net avoided emissions of 4.6 tCO2-eq/ha in Petén (Guatemala) and 2.15 tCO2-eq/ha in Acre (Brazil). While these net avoided emissions were lower than in previous years, they seem to be driven by a reduction in carbon emissions outside Community Managed PAs. Spatially, the boundaries of Community Managed PAs varied across jurisdictions. For example, the boundaries of Acre’s Community Managed PAs’ have become less effective in avoiding emissions, which translates into reduced effects on conserving carbon stocks. Our results highlight the need to assess temporal effects to exhibit jurisdiction-wide land-use dynamics and spatial effects to identify local land-use pressures emerging inside or around the boundaries of PAs. Our analysis also shows that decentralized governance in Community Managed PAs may contribute to climate change mitigation through REDD+ and forest conservation targets.